Rhino mania in the Western European Art of the 18th Century - Klyushina, Elena V. (Actual Problems of Theory and History of Art, 2018)
The present article is devoted to a brief study of the iconographic features of rhinoceros in the Western European art of the 18th century. Following Tim Clarke, the author uses the term “rhino mania”, which, according to the researchers, most accurately represents a special phenomenon in the European culture of modern and contemporary history, characterized by an increased public interest and, in turn, the artistic and aesthetic demand for rhinoceros images. Touching upon the iconographical primary source, the peculiarities of the artistic archetype genesis, and its mode of representation by the greatest masters of the 15th-17th centuries, the author goes on to analyze the key works of painting, graphics and decorative art of the 18th century, demonstrating the gradual debunking of the myth created by A. Dürer. In view of the topic the paper deals in detail with the individual works by such masters as Jan Wandelaar, Johann Elias Ridinger, Jean-Baptiste Oudry, and Pietro Longhi. Their sequence corresponds to the geography of the European voyage of Clara, the rhinoceros, which was brought to Europe by the Dutch in 1741 and became a true sensation for the Europeans. The author also pays sufficient attention to the question of the nature of the emergence of “rhino mania”, seeing its source primarily in the changes in the economic and, consequently, the expositional order.